Buckling and vibration analysis of compressively loaded coil springs by finite element method - Tan, Tedrick Heng Wee (Nanyang Technological University, 2023)
In numerous mechanical applications, compression coil springs are widely used. An example would be the automotive suspension systems. In such applications, the springs are subjected to compressive loads, as well as vibrations and shocks. It is thus important to investigate the performance characteristics of compression coil springs such as the critical buckling load and natural frequencies.